2017
DOI: 10.1111/vsu.12662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tourniquet number and exsanguination on amikacin concentrations in the radiocarpal and distal interphalangeal joints after low volume intravenous regional limb perfusion in horses

Abstract: Low volume (10 mL) cephalic IVRLP should be combined with the placement of 2 tourniquets (proximal and distal to the carpus) to achieve therapeutic amikacin concentrations in the RCJ. Exsanguination prior to low volume IVRLP does not alter synovial fluid amikacin concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 15 publications
3
33
0
Order By: Relevance
“…In another study, Kilcoyne et al performed consecutive synovial fluid amikacin concentration measurements during a 30‐minute cephalic IVRLP (pneumatic tourniquet; 450 mm Hg) at 5‐minute intervals and found that the maximum concentration occurred between 10 and 20 minutes. These 3 reports would suggest a minimum 20‐minute tourniquet time for equine IVRLP. Results of the current study support the potential for WRTs to maintain STP for at least 30 minutes when applied at the AB, GK, and MC; however, less limb movement was noted within 0‐20‐minutes than within 0‐30‐minutes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In another study, Kilcoyne et al performed consecutive synovial fluid amikacin concentration measurements during a 30‐minute cephalic IVRLP (pneumatic tourniquet; 450 mm Hg) at 5‐minute intervals and found that the maximum concentration occurred between 10 and 20 minutes. These 3 reports would suggest a minimum 20‐minute tourniquet time for equine IVRLP. Results of the current study support the potential for WRTs to maintain STP for at least 30 minutes when applied at the AB, GK, and MC; however, less limb movement was noted within 0‐20‐minutes than within 0‐30‐minutes.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, consecutive synovial fluid measurements within the same IVRLP trial may be more valuable than those of different trials, even if a cross‐over design is employed. Moser et al and Schoonover et al reported higher synovial fluid amikacin concentrations at a 30‐minute tourniquet application time compared with 15 minutes during the same cephalic IVRLP (pneumatic tourniquet; 420 mm Hg). In another study, Kilcoyne et al performed consecutive synovial fluid amikacin concentration measurements during a 30‐minute cephalic IVRLP (pneumatic tourniquet; 450 mm Hg) at 5‐minute intervals and found that the maximum concentration occurred between 10 and 20 minutes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Little consensus exists regarding how IVRLP should be performed, which limits direct comparisons between studies and the ability to identify sources of variability. There is debate concerning the ideal technical aspects of the procedure (eg, tourniquet type and number, perfusate volume, perfusion time), and the available data are equivocal . The IVRLP performed here was intended to reproduce that easily performed by the general practitioner, and attempts were made to ensure consistency of the procedure and sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…There is debate concerning the ideal technical aspects of the procedure (eg, tourniquet type and number, perfusate volume, perfusion time), and the available data are equivocal. 33,34,[36][37][38] The IVRLP performed here was intended to reproduce that easily performed by the general practitioner, and attempts were made to ensure consistency of the procedure and sample collection. A different methodology could have reduced the variability of the results, but the literature suggests variability is likely regardless of the procedure used.…”
Section: Discussionmentioning
confidence: 99%